Análise experimental e numérica do comportamento de radier estaqueado isolado pré-carregado sob condição inundada - Pereira, Bárbara Estéfany (2025)
This research aimed to understand the behavior of preloaded foundations under flooded soil conditions, resting on collapsible soils in the region of Uberlândia-MG. To achieve this, instrumented static load tests were conducted in conjunction with three-dimensional numerical simulations on real-scale prototypes of an isolated footing with a thickness of 0.20 m and a diameter of 1 m, an isolated pile with a diameter of 0.25 m and a length of 5 m, and a piled raft unit composed of a single pile and a footing with the same dimensions as the isolated foundations. All foundations were subjected to axial compression. Through experimental tests and numerical modeling using Rocscience's RS3 software, it was possible to evaluate the behavior, load transfer and distribution mechanisms, and lateral friction of the foundations, establishing comparisons between them and those studied by other authors. The test results showed a significant reduction in the load-bearing capacity of all foundations when tested under flooded conditions, with reductions of approximately 60% for the isolated pile (EI), 35% for the piled raft unit (REI), 64% for the isolated footing (SI) without preloading, and 24% for the same footing after preloading. Additionally, it was observed that in foundations incorporating footings, preloading before flooding improved the load-bearing capacity due to the reduction of voids in the soil beneath the footing. Based on the observed results, this research provides guidelines for foundation design in areas subject to adverse conditions, contributing to the safety and efficiency of constructions on collapsible soils.